Toward High‐Performance Diamond Electronics: Control and Annihilation of Dislocation Propagation by Metal‐Assisted Termination. Issue 21 (7th November 2019) - Ohmagari, Shinya; Yamada, Hideaki; Tsubouchi, Nobuteru; Umezawa, Hitoshi; Chayahara, Akiyoshi; Mokuno, Yoshiaki; Takeuchi, Daisuke
Abstract : Diamond Science and Technology Metal‐assisted termination (MAT), in which a propagation of dislocations is suppressed by in‐situ metal doping, is proposed. Schottky barrier diodes show improved rectifying action and highly uniform characteristics. A large reduction of dislocation density is successfully captured in 3D image by two‐photon‐excited photoluminescence. More details can be found in article number 1900498 by Shinya Ohmagari and co‐workers.